PENGARUH KESADARAN WAJIB PAJAK, KUALITAS PELAYANAN, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR RODA DUA DI KOTA KUPANG (STUDI KASUS PADA KANTOR SAMSAT KOTA KUPANG) - Nenu, Isabela Julita; Kerihi, Anthon Simon Yohanis; Muga, Maria Prudensiana Leda (Universitas Nusa Cendana, 2025)
The aims of this study are to analyze the factors that influence the compliance level of two-wheeled motor vehicle taxpayers in Kupang City, which include taxpayer awareness, service quality, and tax sanctions. This study uses a mixed-method approach. The sampling technique and informant selection used purposive sampling. In the quantitative approach, data analysis techniques use statistical analysis, which includes data quality tests, classical assumptions, multiple linear regression, and hypothesis testing, while in qualitative data, the techniques used include data reduction, display, and verification. The analysis results found that partially, taxpayer awareness and tax sanctions have a positive and significant impact on tax compliance levels, while service quality shows a positive but not significant impact on taxpayer compliance. Other findings indicate that simultaneously, taxpayer awareness, service quality, and tax sanctions have a significant impact on the compliance levels of two-wheeled motor vehicle taxpayers in Kupang City.